Control of current reversal in single and multiparticle inertia ratchets. - Larrondo, Hilda Angela (2002)
We have studied the deterministic dynamics of underdamped single and multiparticle ratchets associated with current reversal, as a function of the amplitude of the external driving force. Two experimentally inspired methods are used. In the first method the same initial condition is used for each new value of the amplitude. In the second method the last position and velocity is used as the new initial condition when the amplitude is changed. The two methods are found to be complementary for control of current reversal, because the first one elucidates the existence of different attractors and gives information about their basins of attraction, while the second method, although history dependent, shows the locking process. We show that control of current reversals in deterministic intertia ratchets is possible as a consequence of a locking process associated with different mean velocity attractors. An unlocking efect is produced when a chaos to order transition limits the control range.